2006
DOI: 10.1186/1742-4933-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Ageing is associated with a decline in peripheral blood CD56bright NK cells

Abstract: Background: Natural killer (NK) cells are cytotoxic lymphocytes that lack CD3 and express variable levels of CD16, CD56 and CD57. In recent years NK cells have been categorised into two major groups based on the level of CD56 expression. This phenotypic classification correlates with functional activity as CD56 bright NK cells are the major cytokine producing subset whereas CD56 dim NK cells exhibit greater cytotoxic activity. Previous studies have revealed a reduction in total NK cell numbers in association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 26 publications
6
62
1
Order By: Relevance
“…The higher mature NK subset seen in the nursing home elderly in our study is consistent with immunosenescence studies including community dwelling elderly [34,35]. These results support the observation that the increase in NK cells seen in the elderly is due to accumulation of mature NK cells.…”
Section: Discussionsupporting
confidence: 92%
“…The higher mature NK subset seen in the nursing home elderly in our study is consistent with immunosenescence studies including community dwelling elderly [34,35]. These results support the observation that the increase in NK cells seen in the elderly is due to accumulation of mature NK cells.…”
Section: Discussionsupporting
confidence: 92%
“…[158] The number of Vδ1 cells is not changed with aging [158], rendering its relative expansion within the γδ-T cell population. On the other hand, with increase in age, there is an increased number of CD56 dim NK cells (high NK activity) [159] and a decreased number of CD56 bright NK cells [160]. However, the total NK cell number is relatively stable at different ages.…”
Section: Non-malignant Clonal Lymphocyte Expansion Versus Lgl Leukemiamentioning
confidence: 99%
“…It has been shown that percentage of CD56 dim NK cell subset (the main subset of NK cells and most cytotoxic) is increased (12, 13) or maintained (14) by age, whereas percentage of immature CD56 bright NK cells is decreased (1215). On the other hand, the expression of different receptors on NK cells is also altered in aging (1618).…”
Section: Introductionmentioning
confidence: 99%